Malignant hyperthermia (literature review) - R. R. Tukhvatullina; N. V. Matinyan (Вестник анестезиологии и реаниматологии)
The objective – to summarize the current literature data on the etiology, pathogenesis, diagnosis and treatment of malignant hyperthermia.   The search and analysis of literature data on malignant hyperthermia in the medical information systems PubMed, Сochrane librarу, Cyberleninka for the last 10 years was performed with using the keywords: «malignant hyperthermia», «dantrolene», «general anesthesia», «succinylcholine», «inhalation anesthetics». The search criteria were met by 96 publications. In addition, references to selected articles were manually checked for applicable articles including recent reports of malignant hyperthermia, in addition to works of historical significance. It was shown that malignant hyperthermia develops in susceptible individuals during or after general anesthesia with the use of trigger agents – inhaled halogen-containing anesthetics and succinylcholine. Until recently, the problem of treatment in Russia remained unresolved, since specific therapy for this syndrome was not available. In connection with the official registration of Dantrolene in the Russian Federation, this problem no longer has a life-threatening potential. Doctors should recognize the symptoms of this disease as early as possible in order to quickly begin the pathogenetic treatment of malignant hyperthermia in order to prevent fatal complications. The material is intended for a wide audience of anesthesiologists, resuscitators and surgeons who may encounter this pathology in clinical practice.